Evaluasi Pemanfaatan Limbah Pertanian sebagai Pakan Alternatif untuk Kambing Peranakan Etawa - Ahmad Ridwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Agricultural by-products are increasingly considered as sustainable feed alternatives for ruminants, especially in regions with limited access to commercial feed. This study evaluates the utilization of various agricultural wastes such as rice straw, corn stover, and peanut haulms as alternative feed resources for Peranakan Etawa (PE) goats. The objective was to assess the nutritional potential, palatability, and impact on goat growth performance. A descriptive qualitative approach was combined with field observations and laboratory proximate analysis. Data were analyzed to compare nutrient contents with conventional feed standards. Results showed that rice straw has high fiber content but low protein (3–4%), while corn stover and peanut haulms offer moderate protein values (6–10%) with acceptable palatability. The integration of these by-products into goat diets demonstrated potential to reduce feed costs by up to 30% without significantly affecting weight gain when properly supplemented. It can be concluded that agricultural by-products are viable feed alternatives for PE goats, particularly in rural areas, though supplementation with protein-rich sources remains essential. This study highlights the economic and environmental benefits of optimizing local agricultural residues as livestock feed.